ах² + bx + c = 0 - общий вид квадратного уравнения
0,3х² = 7,5
0,3х² - 7,5х = 0 | : 0,3
х² - 25х = 0
D = b² - 4ac = (-25)² - 4 · 1 · 0 = 625 - 0 = 625
√625 = 25
х = (-b±√D)/2а
х₁ = (25-25)/(2·1) = 0/2 = 0
х₂ = (25+25)/(2·1) = 50/2 = 25
ответ: (0; 25).
- - - - - - - - - - - - - - - - - - - - - - -
а² - b² = (a - b)(a + b) - разность квадратов
1/4х² - 25 = 0
0,25х² - 5² = 0
(0,5х)² - 5² = (0,5х - 5) · (0,5х + 5) = 0
0,5х - 5 = 0 и 0,5х + 5 = 0
0,5х = 5 0,5х = -5
х = 5 : 0,5 х = -5 : 0,5
х₁ = 10 х₂ = -10
ответ: (-10; 10).
Объяснение:
Формулы:
1) (a- b)(a + b) = a² - b²
2) a² + 2ab + b² = (a + b)²
3) a² - 2ab + b² = (a - b)²
4) a³ - b³ = (a-b)( a² +ab + b²)
5) a³ + b³ = (a+b)( a² -ab + b²)
(k + 3)(k - 3) = k² -3² = k² -9 (формула 1)
(3k - 1)² = (3k)² -2*3k *1 +1² = 3k² -6k +1 (см.3)
16 - 8k + k² = 4² - 2*4*k +k² = (4 -k)²
25k² - 1 = (5k)² -1² = (5k-1)(5k + 1)
(k + 1)(k² -k +1) = k³ +1 (фор.5)
(7a - 1)² = (7a)² - 2*7a*1 + 1² = 49a² - 14a + 1
(2a + 1)(1 - 2a) = (1 +2a)(1 - 2a) = 1 - 4a²
a² +2*3*a + 3² = (a + 3)²
81a² - 1 = (9a)² -1² = (9a - 1)(9a + 1)
125 + a³ = 5³ + a³ = (5 + a)( 5² -5a + a²) = (5 +a)( 25 - 5a +a²)
(2a - 1)(4a² +2a + 1) = (2a)³ - 1 ³ = 8a³ - 1
ах² + bx + c = 0 - общий вид квадратного уравнения
0,3х² = 7,5
0,3х² - 7,5х = 0 | : 0,3
х² - 25х = 0
D = b² - 4ac = (-25)² - 4 · 1 · 0 = 625 - 0 = 625
√625 = 25
х = (-b±√D)/2а
х₁ = (25-25)/(2·1) = 0/2 = 0
х₂ = (25+25)/(2·1) = 50/2 = 25
ответ: (0; 25).
- - - - - - - - - - - - - - - - - - - - - - -
а² - b² = (a - b)(a + b) - разность квадратов
1/4х² - 25 = 0
0,25х² - 5² = 0
(0,5х)² - 5² = (0,5х - 5) · (0,5х + 5) = 0
0,5х - 5 = 0 и 0,5х + 5 = 0
0,5х = 5 0,5х = -5
х = 5 : 0,5 х = -5 : 0,5
х₁ = 10 х₂ = -10
ответ: (-10; 10).
Объяснение:
Формулы:
1) (a- b)(a + b) = a² - b²
2) a² + 2ab + b² = (a + b)²
3) a² - 2ab + b² = (a - b)²
4) a³ - b³ = (a-b)( a² +ab + b²)
5) a³ + b³ = (a+b)( a² -ab + b²)
(k + 3)(k - 3) = k² -3² = k² -9 (формула 1)
(3k - 1)² = (3k)² -2*3k *1 +1² = 3k² -6k +1 (см.3)
16 - 8k + k² = 4² - 2*4*k +k² = (4 -k)²
25k² - 1 = (5k)² -1² = (5k-1)(5k + 1)
(k + 1)(k² -k +1) = k³ +1 (фор.5)
(7a - 1)² = (7a)² - 2*7a*1 + 1² = 49a² - 14a + 1
(2a + 1)(1 - 2a) = (1 +2a)(1 - 2a) = 1 - 4a²
a² +2*3*a + 3² = (a + 3)²
81a² - 1 = (9a)² -1² = (9a - 1)(9a + 1)
125 + a³ = 5³ + a³ = (5 + a)( 5² -5a + a²) = (5 +a)( 25 - 5a +a²)
(2a - 1)(4a² +2a + 1) = (2a)³ - 1 ³ = 8a³ - 1